PELATIHAN PRODUKSI DAN PEMASARAN HASIL OLAHAN UBI UNGU - Giawan Nur Fitria; Riaty Handayani (Jurnal Abdi Masyarakat (JAM), 2017)
Our community service program aims to provide insight and knowledge for housewives in RT 02-07 South Meruya in developing purple sweet potato products in entrepreneurship. The benefits of this activity is to provide counseling to determine the selling price of purple sweet potato product processing into pudding. With the provision of counseling is very useful for the mothers in entrepreneurship to market the results of purple sweet potatoes with the best selling price, so that the mothers can generate good profits and their family income. The method used in this incident is the extension of the calculation of the selling price, the practice of making purple pudding is practical and economical. With this activity it is expected that the participants can make purple sweet potato pudding which is healthy, economical and practical, determining the best selling price so as to improve their families income.